Assessment the Engineering Characteristics of the Smear Zone around PVDs Using Laboratory Tests (Journal of Engineering, 2019)
Smear zone is usually formed around the prefabricated vertical drains (PVD’s) due to mandrel driving. The geotechnical properties of the soil in this zone exhibit significant changes that affect the performance of the PVD’s. The most relevant property in this respect is the coefficient of permeability. So far, no serious attention is paid to investigate the effects of shearing under large shear strains on the geotechnical properties of the soft soil in Fao region. In this study, an extensive laboratory testing program was conducted to assess the characteristics of the smear zone with an emphasis on the permeability coefficient of Fao soft soil. The results show that the permeability of the smear zone is about 70% of the horizontal permeability of the intact soil. An attempt was made to estimate the extension of the shearing zone in the direct shear test. The analysis results indicate that thickness of the shearing zone is about (2.4) cm.